2008
DOI: 10.1002/psc.1068
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the coupling efficiency of phosphorylated amino acids for SPOT synthesis

Abstract: A high demand of interest concerning binding assays to study the consequences of posttranscriptional phosphorylation may be addressed by peptide array-based methods. A crucial factor for de novo chemical approaches to generate such arrays is the possibility to rationally permutate phosphorylation events along a huge number of sequences. The simple principle behind this advantage is the stepwise synthesis of peptides, which allows the incorporation of either phosphorylated or nonphosphorylated derivates at seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…The peptides were released as amides from the N-CAPE membrane by using our standard two-step cleavage protocol for peptides synthesized on cellulose-bound linkers as reported previously. [38,68] The peptides were each dissolved in acetonitrile/water (1:1, 100 mL).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The peptides were released as amides from the N-CAPE membrane by using our standard two-step cleavage protocol for peptides synthesized on cellulose-bound linkers as reported previously. [38,68] The peptides were each dissolved in acetonitrile/water (1:1, 100 mL).…”
Section: Discussionmentioning
confidence: 99%
“…The determined quality and purity of the SPOTsynthesized peptides are adequate for a reliable screening study. [34,38,39] Importance of peptide length Antibody epitopes usually do not exceed about 15 amino acids in length. However, by using synthetic peptides as antigenic probes, it has been shown that linear peptide epitopes are constructed by two to five critical residues, usually located within a sequence between five and eight amino acids in length.…”
Section: Quality Of Membrane-bound Peptidesmentioning
confidence: 99%
“…SPOT technology simplified the chemical synthesis of peptide arrays to the addressable deposition of reagents on a planar cellulose membrane (filter paper). Moreover, chemical synthesis allows one to incorporate phosphorylated [40], methylated or acetylated amino acids [41,42], use non-natural building blocks [43,44], prepare branched and cyclic structures [45] and label with chromophores or short biological tags such as biotin [46,47].…”
Section: Spot Synthesis and Synthetic Peptide Arraysmentioning
confidence: 99%
“…SPOT synthesis technology (14) was used to synthesize a panel of 51 13-mer peptides corresponding to all the tyrosine residues present in SHP-2, in their nonphosphorylated and phosphorylated forms, on a cellulose membrane (43). Membranes were incubated with the SHP-2 N-SH2/C-SH2 and GRB2 SH2 domains expressed as GST fusion proteins.…”
Section: C459smentioning
confidence: 99%